Black hole blues and other songs from outer space - Levin, Janna 1967- (Alfred A. Knopf, 2016)
"In 1916, Einstein became the first to predict the existence of gravitational waves: sounds without a material medium generated by the unfathomably energy-producing collision of black holes. Now, Janna Levin, herself an astrophysicist, recounts the story of the search, over the last fifty years, for these elusive waves...a quest that has culminated in the creation of the most expensive project ever funded by the National Science Foundation ($1 billion-plus). She makes clear the how the waves are created in the cosmic collision of black holes, and why the waves can never be detected by telescope. And, most revealingly, she delves into the lives and fates of the four scientists currently engaged in...and obsessed with...discerning this soundtrack of the universe's history. Levin's account of the surprises, disappointments, achievements, and risks of this unfolding story provides us with a uniquely compelling and intimate portrait of the people and processes of modern science"...